Mutual conditioning of factors of regional economic integration in Europe - Milos Srzentic (Anali Ekonomskog fakulteta u Subotici, 2020)
This paper looks into one of the basic theoretical concepts of mutual cooperation of regions in Europe, known as the concept of Europe of the Regions. Through it could be observed the influence of non-economic as well as economic factors participating in creating regional economic integration. According to this concept, multiple regions join as members into one region for easier and faster realization of some common functions determined in advance. By itself, during the joining of those regions, impact of available factors of integration in observed regions is directed primarily toward the successful realization of the target function. The concept of Europe of the Regions is analysed in this paper predominantly on examples of joining of multiple border regions from two or more different states into one cross-border region. The results of the research conducted in this paper are presented in its final section, where the attention is particularly focused on current problems creators of macroeconomic policies are faced with in their attempts to establish firmer and more comprehensive connections among border regions.